2015
DOI: 10.1104/pp.15.00450
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Image-Based Phenomics and Association Analysis to Dissect the Genetic Architecture of Temporal Salinity Responses in Rice

Abstract: Salinity affects a significant portion of arable land and is particularly detrimental for irrigated agriculture, which provides onethird of the global food supply. Rice (Oryza sativa), the most important food crop, is salt sensitive. The genetic resources for salt tolerance in rice germplasm exist but are underutilized due to the difficulty in capturing the dynamic nature of physiological responses to salt stress. The genetic basis of these physiological responses is predicted to be polygenic. In an effort to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
148
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 149 publications
(157 citation statements)
references
References 82 publications
9
148
0
Order By: Relevance
“…1). Comparing the percentage decrease in salt-treated plants relative to control plants at each interval, consistent with the results of Campbell et al 16, we found that indica lines maintained better growth than aus lines (Fig. 1c,d; Supplementary Table 1); for example, in the interval 2–6 days after treatment, growth of indica due to salinity decreased by 21%, while that of aus decreased by 29%.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…1). Comparing the percentage decrease in salt-treated plants relative to control plants at each interval, consistent with the results of Campbell et al 16, we found that indica lines maintained better growth than aus lines (Fig. 1c,d; Supplementary Table 1); for example, in the interval 2–6 days after treatment, growth of indica due to salinity decreased by 21%, while that of aus decreased by 29%.…”
Section: Resultssupporting
confidence: 91%
“…To date, few genetic studies have used high time- and spatial-resolution non-destructive image-based phenotyping to address the complex response of plants to abiotic stresses1316. In this work, we have demonstrated the effectiveness of high-throughput phenotyping for dissecting the genetic architecture of complex traits such as RGR, TR and TUE, and the effects of salinity on these parameters.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, Campbell et al [32] conducted an association analysis on 360 rice lines with 26 258 SNPs to understand the genetic mechanism of the dynamics of rice responses to salt stress. The…”
Section: Splinementioning
confidence: 99%
“…A variety of noncommercial platforms and methods developed by the research community also exist and have been demonstrated to perform well (White et al, 2012;Fiorani and Schurr, 2013;Sirault et al, 2013;Pound et al, 2014). Several platforms have been deployed at sufficiently large scale to examine genomic loci underlying complex traits in crop plants such as barley (Hordeum vulgare; Honsdorf et al, 2014), pepper (Capsicum annuum; van der Heijden et al, 2012), maize (Zea mays; Liu et al, 2011), rice (Oryza sativa; Campbell et al, 2015), and wheat (Triticum aestivum; Rasheed et al, 2014). These successful applications of image-based phenotyping to understand the genetic bases of complex crop traits represent only a small fraction of the imaging modalities and crop species available for study.…”
mentioning
confidence: 99%